The effect of problem based learning on students' mathematical literacy ability - Andini, Fadhila Andini; Siregar, Machrani Adi Putri (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research is motivated by the many problems that often arise during learning in the classroom, especially mathematics. The purpose of this study was to determine how the description of students' abilities and problems in learning mathematics about relations and functions is taught using problem-based learning models and conventional learning models. With a post-test-only control group design, this research is quasi-experimental. Based on the results of data analysis obtained sig. (2-tailed) of 0.000 <0.05. Therefore, it can be concluded that Problem Based Learning and conventional learning produce significantly different levels of mathematical literacy. The practical implication of this study is that educational practitioners, particularly mathematics teachers at the junior high school level, can utilize these findings to improve their teaching. PBL can be used as a basis for designing more innovative and student-centered learning units, which can help students develop a deeper understanding of mathematical concepts and improve their ability to solve problems. Adequate support and training for teachers in implementing PBL is also important to ensure its successful implementation in the classroom.